Simplicity, Price, Quality of Service and Safety Towards The Decision to Purchase Products Through Shopee.id Application - Nursiam Nursiam; Anastasia Auti Merry Yanissa; Kurnia Rina Ariani (Universitas Muhammadiyah Surakarta, 2020)
This study aims to determine the effect of convenience, price, service quality and safety on product purchasing decisions through the shopee.id application. The method used in this study is a quantitative method. Respondents in this study were accounting students for the 2016 class of the Faculty of Economics and Business, University of Muhammadiyah Surakarta, where sampling used the incidental sampling method, with a total sample of 81 respondents. Data analysis techniques used multiple linear regression models. The results of this study indicate that ease, price, and quality of service affect the product purchase decision through the Shopee.id application with each sig value of 0,033; 0,000; and 0,000. Meanwhile, security has no effect on product purchasing decisions through the shopee.id application with a sig value of 0,087. Keywords : ease, price, quality of service, security, decision on purchasing product.